Safety critical systems handbook : a straightforward guide to functional safety, IEC 61508 (2010 edition), IEC 61511 (2015 edition) and related guidance /: a straightforward guide to functional safety, IEC 61508 (2010 edition), IEC 61511 (2015 edition) and related guidance. (2016) - Smith, David J (David John), 1943 June 22; Simpson, Kenneth G. L
No abstract available